Digital Transformation, Financial Performance and Sustainability: Evidence for European Union Listed Companies - Ionaşcu, I.; Ionaşcu, M.; Nechita, E.; Săcărin, M.; Minu, M. (Amfiteatru Economic)
This paper aims to discuss the digitalization of European listed companies in the context of the European Green Deal. The digital transformation can support companies in the field of corporate social responsibility, particularly in terms of environmental protection. Companies’ digitalization may have a beneficial impact by adopting ‘smart’ technologies that allow for the efficient use of natural resources and the reduction of pollution, enabling the transformation of business models into sustainable ones within the circular and digitized economy. Based on a large sample of companies listed on the main European Union financial markets, this paper aimed at analysing the extent to which digitalization efforts are part of the companies’ general tendencies of becoming good corporate citizens, especially in regard to environmental protection. The study also showed that digitalization efforts are rewarded in financial markets, with investors providing more capital to companies that digitize their activities and are more socially responsible.